Utilization of AIS Satellite Data as Behavior Information Towards Interruption Violations in the Makassar Straits (pp. 1-16) - James Julian; Tri Hadinata; Lukman Yudho Prakoso; Kasih Prihantoro; Demo Putra (JURNAL KEAMANAN NASIONAL, 2023)
Indonesia is the world's largest archipelagic country, with a coastline of 81,000 km. Indonesia's beaches and seas are rich in natural resources, especially marine commodities in the form of fish. The abundance of fish in the Indonesian seas has led to crimes committed by domestic ships not equipped with documents and foreign vessels. In this study, the authors will analyze the causes of criminality in the Makassar Strait, then the process of monitoring maritime security using an AIS Satellite. Enforcement carried out by stakeholders related to the sea and maritime security. This research method uses a qualitative descriptive approach to describe data from AIS satellites in the Makassar Strait. Then it is used to determine which ships are initially identified as committing a violation. This information is used to act effectively, efficiently, and appropriately on sea breaches. This method is expected realization that institutions and stakeholders can work together to patrol at sea and promptly act against violations at sea. The discussion location is in the Makassar Strait because the area borders other countries and is one of the locations for abundant fish resources and international shipping lanes. The data for identifying ships suspected of committing crimes in the Makassar Strait was processed from 2019 to 2022. The violations include 22 smuggling ships, 13 drug smuggling ships, and 12 offending crime ships. From the data, it is a significant violation. Thus, from the analysis results, it is better to need the right timing in implementing patrols and the appropriate momentum for enforcement. Therefore, using AIS Satellite is expected to help and improve law enforcement in that location.